1985
DOI: 10.1254/jjp.38.161
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of 12-O-Tetradecanoylphorbol-13-Acetate-lnduced Increase in Vascular Permeability in Mouse Skin by Lipoxygenase Inhibitors

Abstract: Abstract-The painting of mouse dorsal skin with 12-O-tetradecanoylphorbol-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 33 publications
3
17
0
Order By: Relevance
“…The results are consistent with our previous observation, i.e. possible involvement of lipoxygenase prod uces) in the mechanism of the TPA-induced inflammation [15]. Both TMK688 and TMK777 have a struc ture of diphenylpyraline in their moiety (see fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results are consistent with our previous observation, i.e. possible involvement of lipoxygenase prod uces) in the mechanism of the TPA-induced inflammation [15]. Both TMK688 and TMK777 have a struc ture of diphenylpyraline in their moiety (see fig.…”
Section: Discussionsupporting
confidence: 93%
“…It is well known that a topi cal application of a potent skin tumor promo tor, TPA, to mouse skin induces a nonallergic inflammation, i.e. an increase in vascular per meability and neutrophil infiltration [12,14,15]. In the present study, we demonstrated that both oral and topical administration of TMK688 inhibited TPA-induced inflamma tion, i.e.…”
Section: Discussionsupporting
confidence: 65%
“…Two additional experiments were performed to further characterize the importance of HIF-2α in mediating acute inflammatory responses in vivo. First we induced acute cutaneous inflammation (73,74) by painting ear skin with the TPA. After 24 hours, ears were harvested and analyzed for edema and leukocyte infiltration.…”
Section: Figurementioning
confidence: 99%
“…Acetone (1.4 mL) was added to extract the dye overnight in capped tubes, and the absorbance of the dye was determined spectrophotometrically at 620 nm. This assay is a modi®cation of that used by Nakadate et al [16].…”
Section: Proliferation and Vascular Permeabilitymentioning
confidence: 99%